S103. EXAMINATION OF FORMAL THOUGHT DISORDER AND ITS CLINICAL CORRELATES WITH THE TURKISH VERSION OF THE THOUGHT AND LANGUAGE DISORDER SCALE (TALD-TR) IN SCHIZOPHRENIA. (9th April 2019) - Mutlu, Emre; Kâzım Yazıcı, M; Barışkın, Elif; Ertuğrul, Aygün; Gürel, Şeref Can; Gürkan, Şahin; Göka, Erol; Yagcioglu, A Elif Anil
Abstract: Background: Formal thought disorder (FTD) is considered to be a fundamental feature of schizophrenia (SZ). It is crucial to assess FTD comprehensively in a practical, operationalized way for etiopathogenesis, neurobiology and imaging studies. Kircher and his colleagues (2014) have developed the Thought and Language Disorder (TALD) scale which captures both positive/negative and objective/subjective FTD symptoms. This study aims to analyze psychometric properties of the Turkish version of TALD (TALD-TR) and investigate the relationship between FTD and various clinical characteristics in patients with SZ. Methods: The original TALD manual was adapted into Turkish and applied to a total of 149 participants of which 114 had DSM-5 psychiatric diagnoses (schizophrenia N=70, mania N=20, depression N=24) and 35 were healthy controls. To analyze interrater reliability of the TALD-TR, interviews of 20 patients diagnosed with SZ were recorded on video. The records were viewed and scored by two independent raters. Positive and Negative Syndrome Scale (PANSS), Hamilton Depression Rating Scale, Young Mania Rating Scale, and Clinical Global Impression-Severity Scale were administered to detect illness severity. Results: The principle component analyses revealed that the TALD-TR consisted of four factors including the Objective Positive (OP), Subjective Negative, Objective Negative (ON) and Subjective Positive symptom dimensions which were in line with the original TALD factorial structure. The crohnbach alpha values of the factors were found to be 0.91, 0.78, 0.76, 0.53 respectively. Intraclass correlation coefficient was 0.95. It was concluded that TALD-TR shows strong construct validity and high interrater reliability. The correlation analyses with TALD-TR and PANSS showed that there are significant positive correlations between the TALD-TR total score and the PANSS total and subscale scores. In the SZ group, a strong correlation was found between TALD-TR total score and PANSS Conceptual disorganization item. Following PANSS items, which were highly correlated with TALD-TR total score, were Stereotyped thinking, Suspiciousness, Delusions and Unusual thought content. The mania group exhibited the highest mean total score in the OP, whereas the SZ group exhibited the highest mean total score in the ON factor. In the SZ group, age controlled partial correlation analysis revealed that there was a positive correlation between the TALD-TR total score and the duration of illness. A negative correlation was found between the TALD-TR total score and age at illness onset. Additionally, clozapine users had higher TALD-TR ON score than non-clozapine users. Discussion: This study showed that TALD-TR is a valid and reliable tool with good psychometric properties to assess FTD by its unique four-factorial structure as in the original study. The correlation between FTD and PANSS items associated with thought content suggest that thought content and thought process are not completely discrete entities. The comparison of FTD among different diagnostic groups showed a distinct pattern regarding the TALD-TR factors. In line with literature, the results of this study suggest that FTD is related with higher illness severity, longer duration of illness and early age at illness onset in patients with SZ. These findings emphasize the need to develop new treatment strategies aiming to improve FTD from the early stages of SZ. In patients with treatment refractory schizophrenia, especially the Objective Negative symptoms remain to be one of the main treatment targets. Finally, successful adaptation of TALD into different languages seems to be possible, bringing in an international tool for research on FTD.